The discarded image : an introduction to medieval and Renaissance literature - Lewis, C. S. (Clive Staples), 1898-1963 (Cambridge [England] : University Press, 1964)
C.S. Lewis's The Discarded Image paints a lucid picture of the medieval world view, as historical and cultural background to the literature of the middle ages and renaissance. It describes the 'image' discarded by later ages as 'the medieval synthesis itself, the whole organisation of their theology, science and history into a single, complex, harmonious mental model of the universe'
1. The medieval situation -- 2. Reservations -- 3. Selected materials: the classical period: The Somnium Scipionis -- Lucan -- Statius, Claudian, and the Lady Natura -- Apuleius, De Deo Socratis -- 4. Selected materials: the seminal period: Chalcidius -- Macrobius -- Pseudo-Dionysius -- Boethius -- 5. The heavens: The parts of the universe -- Their operations -- Their inhabitants -- 6. The Longaevi -- 7. Earth and her inhabitants: The Earth -- Beasts -- The human soul -- Rational soul -- Sensitive and vegetable soul -- Soul and body -- The human body -- The human past -- The seven liberal arts -- 8. The influence of the model
Includes bibliographical references and index
Keywords: Literature, Medieval -- History and criticism; Latin literature, Medieval and modern -- History and criticism; European literature -- Renaissance, 1450-1600 -- History and criticism